Práticas pedagógicas na perspectiva dos letramentos digitais: uma pesquisa em colaboração com professoras de língua portuguesa nos anos iniciais do ensino fundamental - Ramos, Andréia Ruth Fortaleza (2024)
This study as a general objective aimed to analyze the pedagogical practices from the perspective of digital literacy revealed by Portuguese language teachers in reflective training cycles, and as with specific objectives: to understand teachers' understandings regarding working with digital literacy in teaching Portuguese language; characterize the pedagogical practices carried out by Portuguese language teachers, changing the perspective of digital literacy; and analyze the proposals highlighted by teachers concerning practices aimed at the perspective of digital literacy. Hence, the theoretical bases of our study can be found in Street (2014), in order to talk about social literacies; Kleiman (1995; 2007), when discussing literacy; Lankshear and Knobel (2007; 2008) and Buzato (2009), on digital literacies; Buzato (2006), Hissa (2021) and Ribeiro (2016), in order to talk about teacher training and digital literacy; and also Geraldi (2011) and Antunes (2003), in order to discuss Portuguese language teaching from an interactionist perspective. For the methodology of our study, we took over a collaborative approach from the perspective of Desgagné (2007), and the procedures used were based on Ibiapina and Ferreira (2003;2005) and Ibiapina (2008;2016). Therefore, our methodology consisted of inviting Portuguese language teachers to join us in a process of reflection on their pedagogical practices carried out from the perspective of digital literacy, with the aim of producing knowledge about teaching action. The results found show us that the teachers' understandings of language and Portuguese language teaching influence the elaboration and achievement of pedagogical practices from the perspective of digital literacy. We also figured out that the textbooks have a great influence on pedagogical practices, as they take up most of the time, and we also found that they offer very few proposals for working with digital literacies. In this way, pedagogical practices for teaching the Portuguese language which aim at the perspective of digital literacy are also few. The teachers also revealed the great difficulty in planning and executing practices from the perspective of digital literacy, as teacher training does not offer theoretical or practical support for the construction of these practices. Besides these results, through reflective cycles, the teachers were able to point out possibilities related to expanding their practices from the perspective of digital literacies, identify possibilities within their context that can be an alternative to the difficulties encountered when working with digital literacies, as well as launch perspectives regarding broader possibilities, which do not depend on the school context to occur, but which are necessary to guarantee the long-term implementation of pedagogical practices for teaching the Portuguese language from the perspective of digital literacy. And, finally, the collaborative research approach provided teachers with a space to study and reflect on their teaching, enabling them to become familiar with the concept of digital literacy, expanding their conceptions of working with this literacy in language teaching. Portuguese. Furthermore, it was possible to perceive possibilities for carrying out work with digital literacy in Portuguese language teaching.